Innovating critical reading through HOTS-based digital books: A mixed-methods study of the FIVES strategy among EFL university students - Hidayanto, Habibi Nur; Sumardjoko, Bambang; Sutopo, Anam (Jurnal Cakrawala Pendidikan, 2026)
The growing demand for critical reading skills in 21st-century education requires innovative teaching approaches that not only develop comprehension but also foster higher-order thinking. However, many EFL students still perceive reading as a passive activity, limiting their ability to engage with complex texts. This study explored the effectiveness of HOTS-based digital books integrated with the FIVES strategy in enhancing students’ critical reading abilities. Using a mixed-methods design, 60 first-semester EFL university students from two institutions in Central Java were divided into experimental and control groups. Quantitative data were collected through pre-tests and post-tests, while qualitative insights were obtained via questionnaires and observations. The results showed a significant improvement in the experimental group’s post-test scores (from 71.47 to 85.68), as supported by an independent-samples t-test (p < 0.05) compared to a modest gain in the control group. Students also reported greater engagement and increased awareness of reading as an active, reflective process. These findings confirm the effectiveness of the FIVES strategy embedded in HOTS-oriented digital content and underscore the value of contextualized materials in fostering metacognitive reading skills. The study concludes that pedagogically grounded digital reading innovations can improve learning outcomes and shift students’ mindsets from passive decoding to critical comprehension.